Relational impact of female primary trauma in a military sample - Hamilton, Stacy L. (Kansas State University, 2007)
Events of war have long been considered traumatic and research has found that those exposed to war may develop posttraumatic stress disorder (PTSD) or psychological difficulties. Although research has indicated the instance of increased PTSD and other symptoms in returning Operation Iraqi Freedom/ Operation Enduring Freedom (OIF/OEF) soldiers, it has yet to explore the trauma experiences of their female partners. The current study sought to address this limitation by exploring the ways in which partners’/wives’ primary trauma influenced the marriage relationship. Given the tendency for trauma to negatively influence relationship satisfaction, it was expected that the primary trauma experiences of the female partners of OIF/OEF soldiers would likewise negatively impact relationship satisfaction for both themselves and the soldiers. Results from this study indicated that female primary trauma, particularly trauma related to PTSD symptoms, has an influence on levels of relationship satisfaction, both for female partners and soldiers. Specifically, female partner re-experiencing symptoms were found to most significantly predict their own relationship satisfaction, while female partner arousal symptoms most significantly predicted soldier relationship satisfaction. Understanding female primary trauma may be important given the seeming sensitivity females have for developing PTSD and for experiencing symptoms that are chronic in nature. In addition, female civilian partners may play a key role in helping military families to function well throughout the deployment process given their assumption of major family responsibilities. Further, their emotional wellbeing may be considered a “family affair” due to the role that family relationships may serve in helping individuals cope with trauma, including returning soldiers. Indeed, civilian female partners appear to play a major role in helping military families cope with stresses associated with war and the deployment process. As such, the emotional condition of military families can no longer be considered solely within the realm of soldier trauma or secondary traumatization, but instead include consideration of the influence of female primary traumatic experiences.
Keywords: Military families; Female primary trauma; Relationship satisifaction; Psychology, Social (0451); Sociology, Individual and Family Studies (0628)